2015
DOI: 10.4049/jimmunol.1403046
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD226 Expression on CD8+ T Cells Is Associated with Upregulated Cytokine Production and Endothelial Cell Injury in Patients with Systemic Sclerosis

Abstract: Systemic sclerosis (SSc) is an autoimmune disease characterized by vascular damage and fibrosis of the skin and internal organs. Because activated and oligoclonally expanded CD8+ T cells can be detected in peripheral blood and lungs of SSc patients, effector memory CD8+ T cells may play a critical role for organ involvement in SSc; however, the pathogenic functions of effector memory CD8+ T cells remain incompletely understood. In this study, we performed DNA microarray analysis of the sort-purified effector m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 48 publications
4
38
0
Order By: Relevance
“…They also found this CD8+ T cell production of IL-13 is associated with diffuse cutaneous SSc more so than limited SSc 25 . This has also been verified in a recent study with isolated CD8+ T cells 26 . It has also been shown that CD8+ T cells isolated from patients with SSc mediates increased collagen1A and fibronectin expression in dermal fibroblasts in culture and that this can be blocked by incubation with an anti-IL-13 antibody, but not by an anti-IL-4 antibody or isotype control indicating this is IL-13 specific and not mediated through IL-4.…”
Section: Discussionsupporting
confidence: 77%
“…They also found this CD8+ T cell production of IL-13 is associated with diffuse cutaneous SSc more so than limited SSc 25 . This has also been verified in a recent study with isolated CD8+ T cells 26 . It has also been shown that CD8+ T cells isolated from patients with SSc mediates increased collagen1A and fibronectin expression in dermal fibroblasts in culture and that this can be blocked by incubation with an anti-IL-13 antibody, but not by an anti-IL-4 antibody or isotype control indicating this is IL-13 specific and not mediated through IL-4.…”
Section: Discussionsupporting
confidence: 77%
“…The involvement of CD226 in the production of cytokines by immune cells has been mostly studied in NK and CD8 + T cells. CD226 + CD8 + T cells have been shown to produce more IL-4, IL-5, IL-13, and IFN- than their CD226-negative counterparts (40). In NK cells, CD226 triggers production of IFN-, IL-6, and GM-CSF (38,41).…”
Section: Discussionmentioning
confidence: 99%
“…In SSc, Th2 cells, Th17 cells, Th1 cells, Th22 cells, Treg cells, T follicular helper (Tfh) cells, and CD8 + T cells have all been implicated in the pathogenic process (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). However, no previous studies have used quantitative approaches to enumerate T cell subsets within SSc lesions.…”
Section: Introductionmentioning
confidence: 99%